A Servey on Lexis and Stuctures in English Textboos k for Laos Pupils at High Schools - A Communicative Perspectiv - Sacknalath Phouway (2005)
This research is done in the hope of improving the teaching and learning of English as a foreign language in Lao PDR. the study focuses on : Vocabulary system and structures using in English textbooks at high schools in Lao PDR, Presentation of some limitations, Suggestions for better teaching and learning English English in relation to vocabulary and structures in the Communicative approach. To carry out the study effectively we employ data from course books high schools in Lao PDR, from interviews high education experts' questionnaire. Further studies on matters to the improvement relating teaching and learning English in Lao PDR are also suggest.